The passivity of law competence and constitution in the European court of justice - Corrias, Luigi (Springer eBooks., 2011)
The Passivity of Law: Competence and Constitution in the European Court of Justice opens with a legal account of the competence creep, including the role that the European Court of Justice plays in it and a sketch of the present division of competences and the main principles regulating it. It then discusses the relationship between constituent power and constituted or constitutional power from the viewpoint of the history of constitutional theory before offering an alternative interpretation of their relationship, the chiastic theory, which is based on the philosophical investigations of M. Merleau-Ponty. It details how this chiastic approach can be used to make sense of the Court?s role in the competence creep in general and the doctrine of implied powers in particular, and it utilizes several case studies concerning competences to sustain this claim. Aimed at researchers and practitioners in Philosophy, Phenomenology, Political Science, the Social Sciences and numerous fields of law, this monograph is a seminal work in the evolving theory and practice of EU (constitutional) law.